The acceptance model of M-payment using smartphone devices in Thailand: A conceptual framework - Nakwari, Parisgawin; Kreesuradej, Worapoj; Chaveesuk, Singha (My University, 2018)
In this paper, we have proposed the M-payment method using the smartphone applications, from which all electronic transactions such as purchasing, sales and the provision of other financial services can be applied. This is the investigation of the UTAUT2 extended theory that can be more appropriate for the consumers. The UTAUT2 extended theory is integrated with the service quality, which can be used to examine the acceptance potential of the M-Payment user by smartphone devices. The outcomes of this study will benefit the financial industry in their effort to initiate an extensive online-payment process in all users, especially, in Thailand.
Keywords: Digital transactions; M-Payment; PIIT; Service quality; UTAUT2